Microbiological Monitoring of Purulent Complications in Burn Patients and Molecular Genetic Features of Methicillin-Resistant Staphylococcus aureus (MRSA) - O. E. Khokhlova; O. V. Peryanova; I. V. Vladimirov; V. A. Matskevich; N. K. Potkina; D. N. Kapshuk; L. N. Kopytko; V. V. Gostev; S. V. Sidorenko; Ya. .. Iwao; T. .. Yamamoto (Антибиотики и Химиотерапия)
The aim of the study was to research the microflora of suppurative complications, its antibiotic resistance, and the molecular genetic features of MRSA in burn patients. Material and methods. The microflora of biopsy specimens, wound fluid from 145 patients with thermal burns was investigated on the first day and on the 10-50th days of stay in the burn center of the Regional Clinical Hospital in 2013-2016. The molecular genetic features of 12 strains of MRSA isolated from different burn patients have been studied. Methods used: bacteriological, PCR, M-PCR, sequencing, PFGE, agglutination reaction. Results. On the first day of hospitalization, when biopsy specimen and wound fluid were taken, microbial growth was detected in 25.5% of cases, gram-positive microorganisms, in particular MSSA (37.8%), dominated. On the 10-50th days of hospitalization, growth was obtained in 93.2% of cases, Gram-negative microflora (53.4%) dominated, with a significant role played by Pseudomonas spp. and Acinetobacter spp. (38.0%), characterized by a high degree of resistance to antimicrobial drugs: XDR - 18%, PDR - 67%. On the 10-50th days of hospitalization, a significant role was played by staphylococci (38.7%), while the proportion of MRSA was 62.2%. Circulation of one MRSA clone in burn patients - ST239/spa3(t037)/a§r//SCCmecIII.1.1.2(IIIA)/CoaIy, characterized by multiple resistance to antimicrobial agents, was established.